University students’ general and specific beliefs about infinity, division by zero and denseness of the number line - Juter, Kristina (NOMAD Nordic Studies in Mathematics Education, 2019)
A study of university students’ beliefs about infinity and related concepts, e.g. division by zero and denseness of the number line, was conducted. The concepts were chosen for the students’ proven cognitive challenge in coping with them, and part of the study was to analyze individual beliefs of the different concepts in relation to each other. A questionnaire was designed to discover relationships between preservice teachers’ and technology students’ beliefs. Particular foci in the study were general and specific perspectives of the concepts and admission requirements for the programs. The results show incoherence with respect to general and specific representations of aspects concerning denseness of the number line, and also show that admission requirements are significant when it comes to validity of beliefs about division by zero.